давай с задачей ок не против
Пошаговое объяснение:
1) (х-2)(х+3)+(x-3)(х+2) = x^2 + x - 6 + x^2 - x - 6 = 2x^2 - 12 = 2(x^2-6);
2) (у-1)(y+2)+(y+1)(у-2) = y^2 + y - 2 + y^2 - y - 2 = 2y^2 - 4 = 2(y^2-2);
3) (a+1)(а+2)+(a+3)(а+4) = a^2 + 3a + 2 + a^2 + 7a + 12 = 2a^2 + 10a + 14 = 2(a^2 + 5a + 7) ;
4) (с-1)(c-2)+(с-3)(c-4) = c^2 - 3c + 2 + c^2 - 7c + 12 = 2c^2 - 10c + 14 = 2(c^2 - 5c + 7).
давай с задачей ок не против
Пошаговое объяснение:
1) (х-2)(х+3)+(x-3)(х+2) = x^2 + x - 6 + x^2 - x - 6 = 2x^2 - 12 = 2(x^2-6);
2) (у-1)(y+2)+(y+1)(у-2) = y^2 + y - 2 + y^2 - y - 2 = 2y^2 - 4 = 2(y^2-2);
3) (a+1)(а+2)+(a+3)(а+4) = a^2 + 3a + 2 + a^2 + 7a + 12 = 2a^2 + 10a + 14 = 2(a^2 + 5a + 7) ;
4) (с-1)(c-2)+(с-3)(c-4) = c^2 - 3c + 2 + c^2 - 7c + 12 = 2c^2 - 10c + 14 = 2(c^2 - 5c + 7).